Moving Forward with ALMPs Active Labor Policy and the Changing Nature of Labor Markets - Romero, Jose Manuel (The World Bank, 2019)
Disruptive factors related to technology, market integration, and social and demographic change imply upcoming changes in the needs of the labor force. This study reviews the current approach to active labor market policies (ALMPs) globally and, based on the evidence and accounting for these factors, discusses desirable attributes for a resilient national active labor policy system, which covers universal access, tailored beneficiary service bundles, private sector linkages, using available technology, demand-driven skills training, measuring performance, social enterprises, and labor market demand side policy. Considering these attributes, we propose a public sector approach focused on supporting service providers rather than direct service provision. The approach revolves around: (i) Active Labor Policies (ALPs), referring to public expenditures on services aimed at improving the labor force's engagement in productive economic activity; (ii) Active Labor Policy Providers (ALPPs), referring to the entities that implement activities associated with ALPs; and (iii) the ALPP sector, referring to the set of existing ALPPs in a country. We also highlight potential actions by governments to transition into this model, such as contracting services out; service brokerage; service provider registries, accreditation, and incentives; integrated monitoring and evaluation systems; and aligning supply and demand side policy